Microbial Biofilms Methods and Protocols - Donelli, Gianfranco.; Donelli, Gianfranco. (Methods in Molecular Biology, 2014)
The discovery that most of the chronic infections in humans, including the oral, lung, vaginal and foreign body-associated infections, are biofilm-based, has prompted the need to design new and properly focused preventive and therapeutic strategies for these diseases. Microbial Biofilms: Methods and Protocols provides a detailed description of the currently available methods and protocols to investigate bacterial and fungal biofilms, exhaustively illustrated and critically annotated in 25 chapters written by authors well known for their experience in the respective fields. The book has joined together microbiologists and specialists in infectious diseases, hygiene and public health involved in exploring different aspects of microbial biofilms as well as in designing new methods and/or developing innovative laboratory protocols. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Microbial Biofilms: Methods and Protocols presents readers with the most established and validated experimental procedures to investigate microbial biofilms.